Analysis of greenery coverage of the area of the City ofWarsaw on the quality of life of residents on the basis of spatial and statistical data - Alina Maciejewska; Janusz Sobieraj; Łukasz Kuzak (Archives of Civil Engineering, 2024)
Biologically active areas play an extremely important role in the structure of a city and increasing their coverage, especially in large urban centres, is an activity with a number of advantages. This article compares, in terms of green spaces, two European cities of similar size – Warsaw (517.2 km2) and Oslo (454 km2). Both cities are capitals of their respective countries but implement different spatial policies in the scope of the Green Deal. In Warsaw, many industrial and post-industrial areas still exist and simultaneously urban green areas are decreasing year by year. In Oslo, a strategy based on deindustrialisation of the city and possible maximum use of urban greenery and public spaces is implemented. The research described in this article involved analysing the coverage of the analysed cities and their districts with biologically active area and then checking the correlation with other indicators that can be affected by this coverage. These included data on the incidence of the most common diseases among residents, the attractiveness of living for the elderly and families with children, as well as air and soil pollution and the occurrence of negative effects of climate change. The correlation of urban space use in terms of the presence of industrial land in relation to currently existing green spaces in the districts concerned was subsequently determined.